Toward integrative approaches to study the causal role of neural oscillations via transcranial electrical stimulation - Valeriia Beliaeva (Nature Portfolio, 2021)
Transcranial electrical stimulation techniques may enable exploration of the role of neural oscillations in the brain. Here, the authors provide a perspective on its potential across systems, species, theoretical and experimental scales.